Pendampingan Menumbuhkan Minat Jiwa Enterpreneur Sejak Dini dengan Jiwa Sadar Pajak Pada Siswa/i SDN Sukorejo Perak - Pramiana, Omi; Susilo, Dwi Ermayanti; Suprapto, Sugeng; Hendrawan, Suluh Agus (Universitas Nusantara PGRI Kediri, 2020)
Entreprenuer education is very important to instill from an early age so that students creatively have a courageous spirit and are able to overcome problems. Apart from being an entrepreneur, students need to be equipped with tax awareness and the importance of taxes from an early age so that when students enter the workforce they are able to become entrepreneurs with an awareness of taxes. The purpose on conducting this socialization and assistance for this activity is so that students of SDN Sukorejo, Perak Subdistrict, are able to have an entrepreneurial spirit from an early age and whether students of SDN Sukorejo Perak Subdistrict, have awareness and understand the importance of taxes from an early age. The method of activity is by means of material socialization and assistance with entrepreneurial activities. The results show that students have an interest in becoming entrepreneurs and are aware of the importance of taxes for all Indonesian people.